Ultrawideband antenna distortion compensation - Malik, W; Stevens, C; Edwards, D (2008)
The radiation characteristics of ultrawideband (UWB) antennas vary with frequency, introducing directionally asymmetric bandwidth reduction and waveform dispersion. In this paper, we develop a simple technique to alleviate the distortion due to nonisotropically dispersive antennas, and use indoor channel measurements to verify its performance. The approach is based on multipath direction estimation and therefore involves antenna arrays. We show that antenna distortion can enhance sensor localization ambiguity and introduce errors in its estimate. Antenna compensation mitigates this effect, significantly improving the location estimation accuracy. We further demonstrate that antenna compensation helps reduce the small-scale fading artifacts that arise due to the antennas, thus reducing the channel spatial variability and delay spread. Our technique can also aid empirical channel characterization by providing antenna-independent propagation data. © 2008 IEEE.